Bulk superconductors textured and densified by Spark Plasma Sintering. Issue 1807 (2015) - Noudem, J. G.; Dupont, L.; Bernstein, P.
ABSTRACT: In this contribution, we report progress in the preparation of superconducting materials made by Spark Plasma Sintering (SPS). On the one hand, the fabrication process was optimized in order to improve the texturing of Bi2 Ca2 Sr2 CuO8 superconductor ceramics. The new process is referred to as "Spark Plasma Texturing" (SPT). During SPT, the bulk material is free to deform itself. As a result, an inter-grain preferential crystallographic orientation is generated, while materials processed by conventional SPS are usually quasi-isotropic. The crystallographic orientation causes a strong anisotropy in the magnetic properties of the Bi2 Ca2 Sr2 CuO8 bulk. On the other hand, superconducting MgB2 discs were consolidated using the rapid SPS process. MgB2 has not been yet been seriously considered as a superconductor that could be used for magnetic levitation. Here we present trapped field measurements as a function of the distance to the superconductor and field cooled levitation force measurements that suggests that it presents interesting characteristics for this application.